Frequency of Various Breast Disorders Presenting in HBS Hospital: A Local Experience - Asma Bibi, Iftikhar Ahmed, Bashir Ur Rahman, Adeel Ur Rehman, Gul Muhammad, Sosan Shahid, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine frequency of different breast disorders in female patients of varying age groups presenting to HBS Hospital Islamabad. Study design: A prospective descriptive study Place and duration: This study was conducted in department of General Surgery HBS Hospital from 1st May 2019 to 31 Dec 2021. Methodology: All female patients presenting to surgical OPD and indoor department from 1st May 2019 to 31 Dec 2021 for different breast diseases with no age limitation were included in the study. Data of the patients as age at presentation, symptoms, clinical features, and risk factors, investigations as ultrasound and specimen reports if any were recorded and submitted for histopathology analysis. Results: A total of225female patients were included in the study. Frequency of the disorders was as follows. Fibroadenoma breast presenting as lump breast was found in (n=69) followed bicyclical mastalgia (n=62),breast abscess (n=27), duct ectasia (n=18), carcinoma breast (n=13),sebaceous cyst breast (n=9), mastitis (n=8), cracked nipples (n=8),non-cyclical mastalgia (n=4),galactorrhea (n=3), breast budding (n=1), phylloides tumor (n=1), blood stained nipple discharge (n=1) and nipple eczema (n=1) in frequency. Age of patients ranged from 9-85 years with mean age 51.5 years. Conclusion: Fibroadenoma is the commonest disease but the pattern is rapidly changing towards fibrocystic disease especially in young females. Incidence of Inflammatory disease increases in peak reproductive age group. Carcinoma breast presents late in our setups. Keywords: Breast Lump, Breast Disease, Carcinoma Breast, Fibroadenoma Breast